2011
DOI: 10.1130/l121.1
|View full text |Cite
|
Sign up to set email alerts
|

Detrital zircon U-Pb geochronology of Paleozoic strata in the Grand Canyon, Arizona

Abstract: We determined U-Pb ages for detrital zircons from 26 samples of Paleozoic sandstone from the Grand Canyon. Cambrian strata yield mainly ca. 1.44 and 1.7-1.8 Ga ages that indicate derivation from nearby basement rocks of the Yavapai Province. Devonian strata contain zircons of 1.6-1.8 Ga, 1.34-1.40 Ga, and ca. 520 Ma, suggesting derivation from the Mazatzal and Yavapai Provinces, midcontinent region, and the Amarillo-Wichita uplift, respectively. Mississippian strata record a major change in provenance, with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
221
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(236 citation statements)
references
References 51 publications
(80 reference statements)
11
221
0
Order By: Relevance
“…Rainbird et al (2012) showed that the Grenvillian zircon age peak is also present throughout the western margin of Laurentia from the Grand Canyon in the south to the Mackenzie Mountains in the north. These far-flung regions with a dominant Grenvillian age signature imply detritus initially shed from the Grenville orogenic belt was transported w4000 km across Laurentia (see also Rainbird et al, 1992;Rainbird et al, 1997;Dehler et al, 2010;Gehrels et al, 2011;Spencer et al, 2012). The key observation from the data summarized on Fig.…”
Section: Increased Preservation Potential?mentioning
confidence: 86%
“…Rainbird et al (2012) showed that the Grenvillian zircon age peak is also present throughout the western margin of Laurentia from the Grand Canyon in the south to the Mackenzie Mountains in the north. These far-flung regions with a dominant Grenvillian age signature imply detritus initially shed from the Grenville orogenic belt was transported w4000 km across Laurentia (see also Rainbird et al, 1992;Rainbird et al, 1997;Dehler et al, 2010;Gehrels et al, 2011;Spencer et al, 2012). The key observation from the data summarized on Fig.…”
Section: Increased Preservation Potential?mentioning
confidence: 86%
“…A recent detrital zircon U-Pb geochronology study of the Paleozoic stratigraphy of the Grand Canyon (Gehrels et al 2011) is useful for comparison with our IC results. Cambrian and Devonian strata of the Grand Canyon contain detrital zircon populations with age peaks at 1.4 and 1.7 Ga.…”
Section: A Pennsylvanian Flux Of Detrital Muscovite and Uplift Of Thementioning
confidence: 99%
“…Starting at the Mississippian Surprise Canyon Formation (relatively thin, locally preserved paleochannels cut into the underlying Mississippian Redwall Limestone), there is a major shift in detrital zircon population that continues through the remainder of the Paleozoic section (see fig. 5 in Gehrels et al 2011). The primary difference is the appearance of detrital zircons with ages in the range of both ∼300-700 Ma and 1-1.2 Ga in Late Mississippian to Permian sediments, that is, considerably younger ages than in Cambrian and Devonian strata.…”
Section: A Pennsylvanian Flux Of Detrital Muscovite and Uplift Of Thementioning
confidence: 99%
See 2 more Smart Citations